Sentidos-e-significados no sistema de atividade monitoria - Aarão, Sirlene Aparecida (2010)
The research aims at investigating how senses-and-meanings are built in the interactions between teacher-researcher and student-monitor about what it is to be a teacher and also about teaching-learning a foreign language, during the planning and development of a monitorship project. The theoretical, philosophical and methodological background that supports this research is the Activity Theory (LEONTIEV, 1978; ENGESTRÖM, 1999; VYGOTSKY, 1930/1998 e 1934/1999) and also the dialogical perspective of language (BAKHTIN, 1929/1999) in order to understand how subjects build and produce knowledge through their actions, in activity systems. Activity theory made it to possible to understand the subject-object relation, mediated mainly through language. The analysis on developmental and interactional engagement between teacher-researcher and student-monitor was based on the expansive learning cycle conception (ENGESTRÖM, 1999) that states that developing means solving or transforming the existing contradictions/problems, and consequently it results in changes in the activity system: the building of a new object and new motive(s), therefore creating new senses-and-meaning to the subject of the activity. This research was carried out in a private teaching institution, situated in the outskirts of Sao Paulo, in a city called Taboão da Serra, the main subjects are the teacher-researcher and the student-monitor. Data were collected during the second semester of 2007, from August to December. The methodological frame is Critical Research of Collaboration (MAGALHÃES, 2006) whose purpose is to analyze the accomplished practices in order to transform actions with a critical and collaborative dimension.The contributions this research could bring are varied, especially related to teacher education in pre-service teaching contexts. These contributions include rethinking about the teacher we want and/or need to form, taking into account that it involves linguistic and didactical competences and the development of reflexive and critical awareness, in a continuous dialogical interaction between theory and practice